Revisiting the test of purchasing power parity and structural breaks of East Asian countries - Yahya, Mohamed Hisham; Amin Noordin, Bany Ariffin; Abdul Hadi, Abdul Razak (Faculty of Economics and Management, Universiti Putra Malaysia, 2011)
This paper re-examines the long-run purchasing power parity (PPP) relationship for five Asian countries’ (Malaysia, Singapore, Indonesia, South Korea and Thailand) relative to US dollars during a period with structural breaks. The result indicates the evidence of PPP for all the countries with relative to the USA after allowing for a single break in the fourth quarter of 2008 and/or in the fourth quarter of 1997. Nevertheless, allowing for multiple breaks is warranted when testing the validity of long-run PPP for Asian countries because there is evidence that Asian countries have been impacted by 1997 Asian crisis and 2008 US financial crisis. The results suggest that if structural breaks are present but being ignored, the conventional Johansen procedure may yield erroneous results and lead policy-makers and arbitragers to make decisions which are less accurate.